2008
DOI: 10.4137/cgast.s1120
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Needle Knife Precut Papillotomy for Inaccessible Bile Duct following Failed Pancreatic Duct Access

Abstract: Aims: To evaluate the safety, effectiveness, success rate and complications of needle knife precut papillotomy for inaccessible bile duct after failed pancreatic ducts access.Methods: Selective common bile duct cannulation was required for 582 patients from November 2004 to May 2008. Precut sphincterotomy was performed in 28 patients (16 male, 12 female; mean age 71). When standard bile duct cannulation was unsuccessful after more than 20 minutes, the bile duct was considered inaccessible. Group A consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The incidence of post-TPS bleeding varies from 3.7 to 5% [ 7 , 16 ], our post-TPS bleeding was 15% which was a little higher and may be due to a small number of cases. Massive post-TPS bleeding was not reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The incidence of post-TPS bleeding varies from 3.7 to 5% [ 7 , 16 ], our post-TPS bleeding was 15% which was a little higher and may be due to a small number of cases. Massive post-TPS bleeding was not reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of pancreatitis without prophylactic stenting after TPS ranged from 5.5 to 21% [ 4 , 7 , 13 ] and reduced to 3.5% if prophylactic pancreatic stenting was performed [ 5 ]. We had 3 cases (15%) of mild pancreatitis, but all of them recovered in 2 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis has shown that the incidence of PEP in patients who underwent precut sphincterotomy was 5.28%, compared with 3.10% ( p < 0.001) in patients who did not [ 24 , 36 ]. Several studies have reported that the incidence of PEP was 5.5–21% [ 55 , 56 , 57 ] in TPS alone and 3.5–4.1% [ 50 , 58 , 59 , 60 ] in prophylactic PD stent placement after TPS. Moreover, the most recent studies have demonstrated that prophylactic PD stenting reduced the incidence of PEP [ 28 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%